Enterprise Scale Continuous Security Validation Models for Regulated Digital Infrastructures - Adetomiwa A. Dosunmu,; Peter Olusoji Ogundele, (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
Regulated digital infrastructures underpin critical economic and societal functions across sectors such as finance, healthcare, energy, and telecommunications. These environments are subject to stringent regulatory requirements, complex threat landscapes, and rapid technological change, making static or periodic cybersecurity assessments increasingly insufficient. In response, continuous security validation (CSV) has emerged as an approach that enables organizations to systematically test, measure, and validate the effectiveness of security controls on an ongoing basis. This paper develops a conceptual and analytical foundation for enterprise-scale continuous security validation models tailored to regulated digital infrastructures. The study positions CSV as a governance-oriented capability rather than a purely technical function, emphasizing its role in demonstrating regulatory compliance, operational resilience, and risk transparency. Building on established principles from continuous assurance, cyber risk management, and automated testing, the paper proposes a structured framework that integrates threat simulation, control performance measurement, and compliance evidence generation. The framework highlights how continuous validation supports proactive risk identification and enables organizations to align security operations with regulatory expectations and business objectives. Methodologically, the paper adopts a conceptual modeling and scenario-based analytical approach, synthesizing insights from prior research, industry practices, and regulatory guidance. The results illustrate how enterprise-scale CSV models enhance visibility into control effectiveness, reduce assessment blind spots, and support more informed governance decisions. The discussion further explores organizational, technological, and regulatory implications of adopting continuous validation at scale, including challenges related to data interpretation, operational integration, and assurance credibility. Overall, the paper contributes to the evolving discourse on cybersecurity assurance by articulating how continuous security validation can be operationalized as a strategic capability in regulated environments. It offers researchers and practitioners a structured lens for understanding CSV as a foundational element of modern digital infrastructure governance rather than a supplementary security tool.
Keywords: Continuous security validation; regulated infrastructures; cybersecurity assurance; enterprise security; compliance analytics